Peranan Kompetensi SDM Usaha Mikro Dalam Meningkatkan Kinerja UMKM Desa Sukalaksana Kampung Tinggar Baru Kecamatan Curug Kota Serang - Nugraha, Yugi Adhari; Saputra, Agung Aditya; Christianto, Reinardus Dwi Prio (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2022)
MSMEs are able to support the economy of our country, because most of the business actors are MSMEs and are able to absorb labor. Curug sub-district is one of the sub-districts in Serang City which is used as one of the central areas of the creative economy by the Serang city government. One of the MSME areas is Sukalaksana village as one of the villages that has creative business potential that is able to support the economy of the surrounding residents. This can be seen from the proliferation of small retail traders, especially in Sukalaksana Village, Tinggar Village, Curug District, Serang City. This writing aims to describe and analyze the importance of the role of micro-enterprise HR competencies in improving the performance of SMEs in Sukalaksana Village Kp. Tinggar Baru Kec. Serang City Waterfall. This research uses qualitative method.